Monstrous mammals - Pallotta, Jerry; Bolster, Rob (New York, NY Scholastic, 2024)
Contains four volumes of the "Who Would Win?" series that introduce facts about mammals, comparing such aspects as their sizes, brain structure, and abilities.
"4 books in 1!"
3.0
1-4
Keywords: Mammals -- Juvenile literature; Predatory animals -- Juvenile literature; Animal fighting -- Juvenile literature; Animal behavior -- Juvenile literature; Rhinoceroses -- Juvenile literature; Hippopotamus -- Juvenile literature; Lion -- Juvenile literature; Tiger -- Juvenile literature; Coyote -- Juvenile literature; Dingo -- Juvenile literature; Walrus -- Juvenile literature; Elephant seals -- Juvenile literature; Mammals; Predatory animals; Mammals; Predatory animals